Clinical risk factors of bevacizumab-related hypertension in patients with metastatic colorectal cancer: a retrospective study - Zheng, Zhuoling; Zhao, Yihong; Xie, Jingwen; Gao, Min; Wang, Yiting; Li, Xiaoyan (Frontiers in Pharmacology, 2024)
Introduction Bevacizumab, a vascular endothelial growth factor (VEGF) inhibitor, is widely used as a first-line treatment for metastatic colorectal cancer (mCRC), with hypertension being a common adverse effect. However, there is limited data on the predisposing factors contributing to bevacizumab-induced blood pressure (BP) elevation. This study aims to identify clinical risk factors associated with bevacizumab-related hypertension in patients with mCRC. Methods This retrospective study included 178 patients treated between January and June 2020. Demographic data and medical histories were extracted from hospital electronic medical records. Results Among the 178 patients, 54 (30.3%) developed bevacizumab-related hypertension, with a median onset time of 48 days. Univariate and multivariate analyses identified pre-existing hypertension [odds ratio (OR), 3.30; 95% confidence interval (CI), 1.56–6.99] and age ≥60 years (OR, 2.04; 95% CI, 1.00–4.17) as independent risk factors for bevacizumab-related hypertension. The area under the receiver operating characteristic (ROC) curve was 0.66 (95% CI, 0.57–0.75, P < 0.001). The median overall survival (OS) for the cohort was 30.53 months (95% CI, 22.23–38.84). No significant differences in OS were observed between patients with and without bevacizumab-related hypertension (31.13 vs. 27.87 months, P = 0.86). Conclusion Pre-existing hypertension and age ≥60 years are significant clinical risk factors for bevacizumab-related hypertension in mCRC patients. Bevacizumab-related hypertension did not affect overall survival. Clinicians should closely monitor BP within the first 2 months of bevacizumab treatment in high-risk patients.